SPECIFIC RELEASE OF JUDGES REMOVAL: GENERAL THEORETICAL CHARACTERISTICS - Tkachenko, D. (Київський національний університет імені Тараса Шевченка, 2019)
In the article the specifics of the removal of judges from office are clarified. The essence of this legal category is revealed. The general theoretical description of removal of judges from office is given. The author points out that the notion of "removal" is more focused on the science of labor law (on dismissal) or criminal procedural law (on preventive measures such as removal from office and temporary removal of a judge from the administration of justice). The current legislation does not operate on the separate concept of “removal of judges”. Today, it is used in the context of such a measure of legal influence as "temporarily removing a judge from the administration of justice." For the term "justice", its definition is also not provided at the level of law, and in theory there is no common understanding. In addition, at the level of the Basic Law, the terms "legal dispute" and "criminal prosecution" are considered as two different categories that are not covered by each other, which is logical in terms of the substantive load of these concepts. It is worth noting that the term "removal of a judge from the administration of justice" is used in the law with the adverb "temporary", despite the fact that the very concept of "removal" already sees its temporary character - this phenomenon exists before certain conditions arise, after the onset of which it exhausts itself.

У статті з’ясовано специфіку відсторонення суддів від посади. Виявлено сутність даної правової категорії. Надано загальнотеоретичну характеристику відсторонення суддів від посади.  Автор зазначає, що поняттю “відсторонення” більшою мірою приділяється увага в межах науки трудового права (щодо відсторонення від роботи), або ж кримінального процесуального права (щодо таких запобіжних заходів, як відсторонення від посади та тимчасове відсторонення судді від здійснення правосуддя). Чинне законодавство не оперує окремим поняттям “відсторонення суддів”. На сьогоднішній день воно вживається в контексті такого заходу юридичного впливу, як “тимчасове відсторонення судді від здійснення правосуддя”.Щодо терміну “правосуддя”, то його визначення також не надається на рівні закону, а в теорії не існує єдиного усталеного розуміння. Крім того, на рівні Основного Закону поняття “юридичний спір” та “кримінальне обвинувачення” розглядаються як дві різні категорії, які не охоплюються одна одною, що є логічним з точки зору змістовного навантаження цих понять. Окремо варто звернути увагу на те, що у законодавстві термін “відсторонення судді від здійснення правосуддя” вживається із прийменником “тимчасове”, незважаючи на те, що саме поняття “відсторонення” уже вбачає його тимчасовий характер - це явище існує до виникнення певних умов, після настання яких воно вичерпує себе.
СПЕЦИФІКА ВІДСТОРОНЕННЯ СУДДІВ ВІД ПОСАДИ: ЗАГАЛЬНОТЕОРЕТИЧНА ХАРАКТЕРИСТИКА
Keywords: judge; work of judges; justice; temporary removal of a judge.; суддя; праця суддів; правосуддя; тимчасове відсторонення судді.